The Impact of Local Labour Market Conditions on Participation in Further Education in England - Damon Clark (Institute for the Study of Labor (IZA), 2002)
Over the past 30 years, participation in Further Education (FE) in England has been markedly counter-cyclical. What is more, it has yet to increase beyond the peak of 70% reached in 1993, much to the concern of policy-makers. An obvious explanation for these facts is the availability of labour market opportunities, as measured by youth unemployment. Other things equal, the higher is youth unemployment, the more inclined young people will be to participate in FE. To assess this claim, we construct a 20-year panel of regional-level data. In line with this simple story, we find youth unemployment effects that are at least twice as large as those previously estimated, and that can explain the absence of any post-1993 increase, at least for boys. Other interesting findings concern the role of national returns to participation for boys, and cohort size for girls.
Keywords: J24; I28; I21; J31; 330; human capital; further education; local labour markets; Weiterbildung; Bildungsverhalten; Regionale Arbeitslosigkeit; Jugendarbeitslosigkeit; Schätzung; Großbritannien